Lessons from the Nahjul-balaghah - Khaminah'ī, ʻAlī (Islamic Propagation Organization, 1984)
On prophethood, based on Nahj al-balāghah, Arabic work by ʻAlī ibn Abī Ṭālib, Caliph, 600 (ca.)-661 ; Shiite interpretation.